Targeting α‐synuclein aggregation and its role in mitochondrial dysfunction in Parkinson's disease. (24th November 2021) - Haque, Md Ezazul; Akther, Mahbuba; Azam, Shofiul; Kim, In‐Su; Lin, Yuxi; Lee, Young‐Ho; Choi, Dong‐Kug
Abstract : Lewy bodies that contain aggregated α‐synuclein in dopamine neurons are the main culprit for neurodegeneration in Parkinson's disease. However, mitochondrial dysfunction has a well‐established and prominent role in the pathogenesis of Parkinson's disease. The exact mechanism by which α‐synuclein causes dopamine neuronal loss is unclear. Recent evidence suggests that aggregated α‐synuclein localises in the mitochondria contributes to oxidative stress‐mediated apoptosis in neurons. Therefore, the involvement of aggregated α‐synuclein in mitochondrial dysfunction‐mediated neuronal loss has made it an emerging drug target for the treatment of Parkinson's disease. However, the exact mechanism by which α‐synuclein permeabilises through the mitochondrial membrane and affects the electron transport chain remains under investigation. In the present study, we describe mitochondria–α‐synuclein interactions and how α‐synuclein aggregation modulates mitochondrial homeostasis in Parkinson's disease pathogenesis. We also discuss recent therapeutic interventions targeting α‐synuclein aggregation that may help researchers to design novel therapeutic treatments for Parkinson's disease.